'A power that deifies the human and humanizes God': the psychodynamics of love and hypostatic deification according to Maximos the Confessor. Issue 1 (15th March 2017) - Salés, Luis Josué; Papanikolaou, Aristotle
ABSTRACT: Maximus the Confessor has been the subject of numerous subsets of the historical, philosophical, and theological disciplines, but the prominent role virtue – and above all else love – plays in his corpus remains vastly underexplored or misunderstood in secondary scholarship. The ascetic thinker's understanding of virtue is fascinating in its own right since it implies and decodes the enormity of his theological vision by serving as the locus in and through which the created and the uncreated encounter each other. But the distinctive edge of his aretology is all the more peculiar by the way in which he forged it from the remaining shards of the late antique philosophical schools and honed it against the theological touchstones of anchorites, monastics, and Biblical commentators. The result was a multilayered theology of virtue that reimagined the place of love in the Christian life and remained a constitutive aspect of Greek monastic practice and lay piety until the fall of Constantinople and beyond. This chapter situates Maximus within the intellectual horizons wherein he expressed his theology of virtue, analyzes the relationship of love to knowledge and personhood, and examines how the virtues, and especially love, function as the mediating principle between divine condescension and human deification.